Effects of Combined High-Protein Diet and Exercise Intervention on Cardiometabolic Health in Middle-Aged Obese Adults: A Randomized Controlled Trial - Chen, Chiao-Nan; Hsu, Kuo-Jen; Chien, Kuei-Yu; Chen, Jeu-Jung (Frontiers in Cardiovascular Medicine, 2021)
Background: Obesity is the main risk factor of cardiovascular diseases (CVD) and metabolic diseases. The middle-aged population is the age group with the highest prevalence of obesity. Thus, improving cardiometabolic health is important to prevent CVD and metabolic diseases in middle-aged obese adults. The aim of this study was to examine the effects of exercise alone or in combination with a high-protein diet on markers of cardiometabolic health in middle-aged adults with obesity. Methods: Sixty-nine middle-aged adults with obesity were assigned randomly to the control group (C; n = 23), exercise group (E; n = 23), or exercise combined with high-protein diet group (EP; n = 23). Individuals in the E and EP groups received supervised exercise training and individuals in the EP group received high-protein diet intervention. Body composition (assessed by dual-energy X-ray absorptiometry), oral glucose tolerance test (OGTT), lipid profiles, and inflammatory markers were determined before and after 12 weeks of intervention. Insulin sensitivity index (ISI0,120) was calculated from values of fasting and 2-h insulin and glucose concentration of OGTT. Insulin-peak-time during the OGTT was recorded to reflect β-cell function. Analysis of covariance with baseline values as covariates was used to examine the effects of the intervention. The significant level was set at 0.05. Results: After 12 weeks of intervention, the E group had a greater percentage of individuals with early insulin-peak-time during the OGTT than that in the C and EP groups (p = 0.031). EP group had lower total cholesterol and triglycerides than that in the C group (p = 0.046 and 0.014, respectively). Within-group comparisons showed that the 2-h glucose of OGTT and C-reactive protein decreased in the EP group (p = 0.013 and 0.008, respectively) but not in the E and C groups; insulin sensitivity improved in the EP group (p = 0.016) and had a trend to improve in the E group (p = 0.052); and abdominal fat mass and total body fat mass decreased in both intervention groups (p < 0.05). Conclusion: Combined high-protein diet and exercise intervention significantly decreased fat mass and improved lipid profiles, insulin sensitivity, glucose tolerance, and inflammation in middle-aged adults with obesity. Clinical Trial Registration: Thai Clinical Trials Registry, TCTR20180913003, 13-09-2018.